2020
DOI: 10.1002/apj.2468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of granite powder on properties of concrete

Abstract: Studies were conducted using varying proportions of granite powder in canal lining concrete to determine the effect on compression resistance, impermeability and freeze–thaw cycling. The concrete microstructure was assessed using mercury intrusion porosimetry, scanning electron microscopy, and other methods. The data indicate the appearance of pore throats and demonstrate that a granite content of 10%–20% reduces the concrete strength, frost resistance, and impermeability based on changes at the microscopic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Further, the dimensional variation of the SCG20, SCC20 and SCC40 concretes was found to be less than 500 µm/m, indicating a high level of resistance to freeze/thaw cycles as defined by ASTM C 666. These results are in line with those of Zhang et al [28].…”
Section: Freeze/thaw Shrinkagesupporting
confidence: 94%
See 2 more Smart Citations
“…Further, the dimensional variation of the SCG20, SCC20 and SCC40 concretes was found to be less than 500 µm/m, indicating a high level of resistance to freeze/thaw cycles as defined by ASTM C 666. These results are in line with those of Zhang et al [28].…”
Section: Freeze/thaw Shrinkagesupporting
confidence: 94%
“…This improved particle packing can lead to a reduction in voids and improve the overall compactness of the concrete, thereby increasing its workability [26][27]. These results contradict those found by Zhang et al [28].…”
Section: Fresh State Propertiesmentioning
confidence: 73%
See 1 more Smart Citation
“…A proper amount of stone powder can improve the strength of the cement and concrete, but excessive mixing causes adverse effects [1,[27][28][29]. Since neither fly ash nor stone powder in the multicomponent composite cementing material prepared in this paper participated completely in the hydration reaction, the residual fly ash formed microaggregates to fill the internal pores of the material, which was similar to the effect of the residual stone powder.…”
Section: Interpretation Of the Resultsmentioning
confidence: 90%
“…These wastes can be used in conventional and novel concretes to preserve the environment and develop sustainability. Hence, limestone and granite waste powders have been extensively used in concretes or mortars as fillers or fine aggregates (Ramezanianpour et al, 2009;Liu and Yan 2010;Singh et al, 2016;Tu et al, 2018;Wang et al, 2018;Chakherlou and Shervani Tabar, 2019;Savadkoohi and Reisi, 2020;Zhang et al, 2020;Lin Chan and Zhang 2023). For instance, Singh et al (2016) reported that the workability of concretes decreases with the substitution of granite waste as fine aggregates (Singh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%